The Learning Crisis in LAO PDR : Challenges and Policy Priorities - Demas, Angela (World Bank, Washington, DC, 2021)
Improving student learning is now the most pressing education challenge facing Lao PDR. While Lao PDR has made impressive advancements in providing children with schooling, levels of student learning have remained low and the quality of education delivery is poor. In 2017, the World Bank conducted the SABER Service Delivery (SABER SD) survey to support the Ministry of Education and Sports (MoES) in its efforts to improve education outcomes. Survey results reveal that student learning in Lao PDR is very low. SABER SD survey results indicate that insufficient student learning leaves the majority of students unprepared for secondary school, as most students are not attaining the knowledge required for the secondary school curriculum. In addition, significant numbers of students are not achieving even the most basic levels of literacy and numeracy. This data support the findings of previous studies that low levels of learning at the primary school level are a major reason parents allow children to drop out of school in early grades or never enroll them in school at all. While alarming results for student learning spanned all ethnicities, the SABER SD survey revealed an urgent need to improve educational equity for students whose mother tongue is not Lao-Tai. Non-Lao-Tai students were also significantly more likely to lack basic skills in literacy and numeracy. The gap in performance between students in rural schools and urban schools is also significant. In summary, continuing to expand school provision will address some of the needs of Lao PDR children, but achieving goals for enrollment, retention, and learning outcomes in those schools requires concerted focus by all education service providers and new investments in improving learning for all children.